Particulate control devices in Kemper County IGCC Project. (November 2019) - Guan, Xiaofeng; Hewitt, Alan; Peng, WanWang; Vimalchand, P.; Nelson, Matt; Pinkston, Tim; Madden, Diane
Abstract: Southern Company has commissioned a 2 × 1 Integrated Gasification Combined Cycle (IGCC) facility in Kemper County, Mississippi. The plant demonstrated the Transport Integrated Gasification (TRIG TM ) technology developed by Southern Company, KBR, and the U.S. Department of Energy (DOE). With a capability of generating up to 524 MW net, the plant also captures CO2 from syngas produced from locally mined Mississippi lignite. Particulate Control Devices (PCDs), designed by Pall Corporation, are a critical component of the TRIG TM gasification process. The PCDs use dry filtration technology to remove essentially all the fine particulates from the syngas before it is sent to downstream processes for further gas clean-up, CO2 capture, and, finally for use in combustion turbines to generate power. The Kemper PCDs are designed to accommodate different types of filter elements for future optimization. The initial installation features the 2.5-meter long iron aluminide (FEAL) filter elements based on the extensive testing experience gained at the Power Systems Development Facility (PSDF). The PCD back-pulse system is equipped with the Coupled Pressure Pulse (CPP TM ) blowback technology developed jointly by Pall's Schumacher Division and Karlsruhe Institute of Technology for online filter element cleaning. It is the first CPP TM application of this scale used for high-pressure, high-temperature filtration in a gasification process. The Kemper facility has achieved integrated operation with production of electricity, CO2, and other by-products from syngas per design specifications. This paper describes the operations, performance, and technical issues of both the PCD and the fines cooling and handling system that were encountered during the installation, unit commissioning, and extended operation with lignite.